Pelatihan Dan Pembekalan, Menumbuhkan Jiwa Enterpreneurship Sejak Dini ( Sma Unggulan Ponpes Selamat Kendal) - Abdul Khafid; Gilang Kharisma Putra; Ripan; Bambang Wahyudi; Wahyu Adi Wibowo (Jurnal AbdiMas Ekonomi Terapan, 2025)
It is important to instill an entrepreneurial spirit from an early age in order to create individuals who are creative and rich in innovation in facing various challenges. By instilling an entrepreneurial spirit, we will learn to be more independent, think critically and be future oriented, so that a mindset will be created regarding how to process and develop raw materials with the knowledge skills we have and then turn them into new works or breakthroughs that have selling value. , in this way we can participate in developing the community's economy. The implementation of SUPERIOR HIGH SCHOOL Education at Modern Ponpes Selamat has a legal basis and fulfills the function of National Education as outlined in Article 3 of Law No. 20 of 2003 concerning the National Education System. The achievement of the Community Service activities (PKM) carried out at the UNGGULAN Modern Islamic Boarding School, Selamat Kendal, is that students will not only have intellectual intelligence, spiritual intelligence but also have an entrepreneurial spirit by increasing the soft skill potential of the students. by using techniques, lectures, discussions and demonstrations Keywords: Community Service, Entrepreneurial Spirit, Soft Skills